tudi Kasus Pertambahan Berat Badan dan Feed Conversion Ratio (FCR) Pada Ayam Broiler di Narti Farm Blitar - Didik Agung Prastio; Dewi Konita; Rico Anggriawan; Rifai Rifai; Fransiskus Y. D. Kadju (JAS, 2022)
This study aimed to determine the weekly weight gain of broiler chickens at Narti Farm Blitar. This research is survey research where data collection is assisted by questionnaires using interview techniques and field observations. Locations and respondents were determined by the purposive sampling method. This research was conducted in a closed house with a population of 8.000 broiler chickens. Analysis of weight gain using the formula for weight in the latest week (grams) minus weight in the previous week (grams) then divided by 7 days. The weight gain of broilers at Narti Farm is between 1,4 to 1,5 kg with a feed conversion ratio of 1,4 and harvesting age between 29 to 30 days. The results showed that the weight gain and feed conversion ratio at Narti Farm Blitar was in accordance with company standards with the implementation of controlled production management. Broiler farming at Narti Farm is a viable business to run.